The Accuracy of Emergency Physicians in Ultrasonographic Screening of Acute Appendicitis; a Cross Sectional Study - Karimi, Ebrahim; Aminianfar, Mohammad; Zarafshani, Keivan; Safaie, Arash (Archives of Academic Emergency Medicine, 2017)
Introduction:Â Diagnostic values reported for ultrasonographic screening of acute appendicitis vary widely and are dependent on the operatorâ€™s skill, patientâ€™s gender, weight, etc. The present study aimed to evaluate the effect of operator skill on the diagnostic accuracy of ultrasonography in detection of appendicitis by comparing the results of ultrasonography done by radiologists and emergency physicians. Methods:Â This prospective diagnostic accuracy was carried out on patients suspected to acute appendicitis presenting to EDs of 2 hospitals. After the initial clinical examinations, all the patients underwent ultrasonography for appendicitis by emergency physician and radiologist, respectively. The final diagnosis of appendicitis was based on either pathology report or 48-hour follow-up. Screening performance characteristics of appendix ultrasonography by emergency physician and radiologist were compared using STATA 11.0 software. Results:Â 108 patients with the mean age of 23.91 Â± 7.46 years were studied (61.1% male). Appendicitis was confirmed for 37 (34.26%) cases. Cohen’s kappa coefficient between ultrasonography by the radiologist and emergency physician in diagnosis of acute appendicitis was 0.51 (95% CI: 0.35 â€“ 0.76). Area under the ROC curve of ultrasonography in appendicitis diagnosis was 0.78 (95% CI: 0.69 â€“ 0.86) for emergency physician and 0.88 (95% CI: 0.81 â€“ 0.94) for radiologist (p = 0.052). Sensitivity and specificity of ultrasonography by radiologist and emergency physician in appendicitis diagnosis were 83.87% (95% CI: 67.32 â€“ 93.23), 91.5% (95% CI: 81.89 â€“ 96.52), 72.97% (95% CI: 55.61 â€“ 85.63), and 83.10% (95% CI: 71.94 â€“ 90.59), respectively. Conclusion:Â Findings of the present study showed that the diagnostic accuracy of ultrasonography carried out by radiologist (89%) is a little better compared to that of emergency physician (80%) in diagnosis of appendicitis, but none are excellent.Â Â